A brief history of antiretroviral therapy of HIV infection: success and challenges - Lucia Palmisano; Stefano Vella (Istituto Superiore di Sanità, 2011)
Unprecedented efforts in the fields of biology, pharmacology and clinical care have contributed to progressively turn HIV infection from an inevitably fatal condition into a chronic manageable disease, at least in the countries where HIV infected people have full access to the potent antiretroviral drug combinations that allow a marked and sustained control of viral replication. However, since currently used treatments are unable to eradicate HIV from infected individuals, therapy must be lifelong, with the potential for short- and long-term, known and unknown, side effects, and high costs for health care systems. In addition, different patterns of unexpected systemic complications involving heart, bone, kidney and other organs are emerging. Although their pathogenesis is still under debate, they are likely to originate from chronic inflammation and immune dysfunction associated to HIV infection. A final consideration regards the dishomogenous pattern of HIV disease worldwide. In fact, access to HIV diagnosis, treatment and care are seriously limited in the geographical areas that are most affected, like Africa, which sustains 70% of the global burden of the infection. This is one of the greatest challenges that international institutions are asked to face today.